PENGARUH METODE PEMBELAJARAN EDUTAINMENT BERBANTUAN MEDIA MONOPOLI TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN MATEMATIKA KELAS III UPT SD NEGERI 060922 MEDAN SUNGGAL - Rumahorbo, Elisabet Jojor; Patri Janson Silaban; Heka Maya Sari Br Sembiring; Nova Florentina Ambarwati; Paska Sriulina Tarigan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low mathematics learning outcomes of third-grade students at UPT SD Negeri 060922 Medan Sunggal on addition and subtraction of thousands. Of 23 students, 16 (69.6%) did not achieve the minimum learning achievement criteria of 70. This study aimed to determine the effect of the edutainment learning method assisted by Monopoly media on students’ mathematics learning outcomes. The study employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 23 students selected through saturated sampling. Data were collected using a 25-item multiple-choice test and a 20-item student response questionnaire. Data analysis included normality testing, correlation analysis, coefficient of determination, and t-test. The results showed that the mean pretest score of 64.35 increased to 82.26 in the posttest. The correlation test yielded r = 0.906, which was higher than r-table = 0.433, indicating a very strong relationship. The coefficient of determination revealed that 82.08% of the improvement in learning outcomes was influenced by the implementation of the edutainment method assisted by Monopoly media. The t-test result showed t = 9.81 > 1.721, indicating that the alternative hypothesis was accepted. Therefore, the edutainment learning method assisted by Monopoly media had a positive and significant effect on students’ mathematics learning outcomes.